Epidemiology of Acute Chagas Disease in Northeast Brazil (Research, Society and Development, 2021)
Objective: To determine the epidemiological profile of patients with acute Chagas disease (DCA) in the Northeast region of Brazil. Methodology: A descriptive epidemiological study, with a quantitative approach, based on secondary data collected in the Notifiable Diseases Information System (SINAN) referring to cases of ACD reported in the states of Northeast Brazil, between 2010 and 2019. All reported cases and registered in the SINAN database, excluding those that did not fit the period defined for this study. The analysis of the results was made through absolute and relative numbers with results presented through tables and graphs. Results: The Northeast is the second region most affected by DCA in Brazil, with a predominance of cases in the state of Maranhão. The sociodemographic profile of patients is mostly composed of adults, browns and females. DCA has a possible form of transmission, mainly orally and without a predominance of the area of residence. In addition, schooling data and the site of infection were impaired, as the information was ignored in most of the reported cases. Conclusion: The study allowed to know the most prevalent epidemiological profile of CAD, focusing on the state of Maranhão and showing the form of oral transmission. Interventions are needed based on policies to improve housing and combat the vector, investigation of oral contamination, and treatment strategies aimed at improving the quality of life of those infected.